Comparison of Clinical Recovery Following Conventional Tonsillectomy Versus Bipolar Vessel Sealing Device in Chronic Tonsillitis: A Case Report - Abdullah, Adnan; Widuri, Asti; Farid, Muhammad; Mujiono, Zuhair Sudrajat Tiyan; Isnaini, Banun Intan (Universitas Ahmad Dahlan, 2025)
Tonsillectomy remains a common surgical intervention for chronic or recurrent tonsillitis, with evolving techniques aiming to minimize complications and accelerate recovery. This case report explores the clinical outcomes of using conventional tonsillectomy compared to the Bipolar Vessel Sealing Device (BVSD) methods. Two male patients, aged 22 and 33, presented with chronic tonsillitis characterized by throat discomfort, odynophagia, and worsening symptoms, including sleep-related breathing difficulties. Both underwent tonsillectomy, one with the conventional Sluder-Ballenger technique and the other with BVSD. Postoperative parameters pain (measured by Visual Analog Scale), bleeding, fever, and time needed to regain the normal diet were monitored for six days. No bleeding or fever was observed in either patient. However, the BVSD technique was associated with significantly lower pain scores, ranging from VAS 5 to 0 by day six, compared to 9 to 3 in the conventional group. Additionally, patients in the BVSD group transitioned to solid food earlier (day 4), while the conventional group required until day 6. These findings suggest improved tissue preservation and faster functional recovery with BVSD. The BVSD technique offers advantages in postoperative pain control and recovery of swallowing function compared to conventional methods. Although limited by small sample size, this case report supports the potential of BVSD as a more patient-friendly and efficient surgical approach for tonsillectomy, warranting further investigation in larger, controlled studies